Processing of heat-treated silicon carbide-reinforced aluminum alloy composites. Issue 3 (17th February 2019) - Rajavel Muthaiah, V.M.; Meka, S.R.; Venkata Manoj Kumar, B.
ABSTRACT: The present study investigates the processing of heat-treated silicon carbide (SiC) particle-reinforced 6061 aluminum alloy (AA) composites. As-received SiC powders were heat treated at 1300ºC, 1400ºC, and 1500ºC in nitrogen atmosphere for 2 h, and the 6061 AA–SiC composites were developed by spark plasma sintering at 560ºC and 60 MPa for 5 min in argon atmosphere. The amorphous silicon nitride is found to form in SiC particles as a result of heating at 1400ºC. The microstructure of the composites exhibited uniform distribution of SiC or SiC/Si3 N4 particles in 6061 AA matrix. Further, the heat-treated SiC-reinforced 6061AA composites exhibited improved mechanical properties. A typical combination of UTS of 240 MPa and elongation of 21% is obtained for the 6061 AA composites prepared using SiC powders heated at 1400ºC.